Aspekte van reg en geregtigheid met betrekking tot gevangenes* - Rooyen, Jan Van (Koers, 1981)
It is submitted that all scientific labour rests on certain presuppositions. It is further submitted that academics should state their presuppositions explicitly and also indicate the consequences thereof. Especially when the concepts o f "justice” or "human rights” are involved, the value system (and its underlying presuppositions) against which the tules of law in question are to be measured, should be slated clearly.